Spatiotemporal Analysis of Surface Temperature Changes and Their Associated Factors in West Java - Sodikin Sodikin (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
Land Surface Temperature (LST) is an important indicator for understanding environmental dynamics associated with regional development and changes in biophysical conditions. This study aimed to analyze the spatial-temporal changes in LST and identify anthropogenic and biophysical factors associated with surface temperature changes in West Java Province during 2014–2026. The analysis was conducted for 2014, 2018, 2022, and 2026 using Landsat 8 and Landsat 9 Collection 2 Level-2 imagery processed through Google Earth Engine. LST was derived from surface temperature data, while the analyzed factors included changes in NDVI, NDBI, built-up areas, building density, elevation, slope, water-body density, and soil moisture. LST changes were analyzed using image differencing and classified into five categories. Pearson correlation analysis was applied to examine the relationships between LST changes and the selected factors. The results showed heterogeneous spatial patterns of LST changes, with increasing temperatures mainly occurring in urban areas, development corridors, lowland regions, and several coastal areas. Changes in built-up areas showed the strongest relative correlation with LST changes (|r|=0.061), although the relationship remained very weak, followed by changes in NDBI (|r|=0.046), while changes in soil moisture showed the weakest correlation (|r|=0.002). Overall, LST changes represent a complex phenomenon that cannot be explained by a single factor. Therefore, a multivariate approach and integrated spatial management are needed to better understand thermal dynamics and support climate-resilient regional development in West Java.